Answer:
(g · f)(4) = 45
Step-by-step explanation:
f(x)=4x+1
g(x)=x² - 4x- 5
(g · f)(x) = 4(x² - 5) + 1
(g · f)(4) = 4(4² - 5) + 1
Following pemdas
(g · f)(4) = 4(16 - 5) + 1
(g · f)(4) = 4(11) + 1
(g · f)(4) = 44 + 1
(g · f)(4) = 45
A if you multiply the divide the. Subtract the add the. Iudjnff
37.88888888 and it just keep repearing so there is no right answer dont foeget to mark me as the best answer
I need to know if you where are you gonna is the day you
Answer:
4 Terms.
Step-by-step explanation:
5x4
6x3
-2x
7 are all of the terms in the expression.